Global compilation of stable carbon (δ13C) and nitrogen (δ15N) isotope values of meso- and bathypelagic fish - Maria Papadimitraki; Sigrún Huld Jónasdóttir (PANGAEA, 2023)
Stable isotope analysis (SIA) has emerged as a valuable tool for understanding the trophic structure of the marine food web and gaining insights into trophic levels and niche. Researchers are increasingly utilizing SIA in studies focused on feeding ecology, particularly in estimating the long-term diets of meso- and bathypelagic fish. To facilitate this research, a global database of published data on stable isotopes, specifically δ13C and δ15N, of meso- and bathypelagic fish was created. The database was constructed by conducting a thorough search on Google Scholar and reviewing the references cited in the retrieved papers. The search primarily involved using popular terms such as stable isotope analysis or feeding ecology in combination with mesopelagic or bathypelagic fish. The resulting SIA database contains δ13C and δ15N values for 95 different species of meso- and bathypelagic fish, belonging to 27 families, with specimens collected between 2004 and 2015. Each entry in the database includes information on the sampling location, month and year of sample collection, taxonomic classifications (phylum, class, order, family), number of samples analyzed, as well as the reference and DOI of the original data source. This global SIA database holds significant potential as a valuable tool and data source for conducting large-scale meta-analyses.